THE ROLE OF BRACHYTHERAPY IN THE TREATMENT OF RETINAL CAPILLARY HEMANGIOMAS - V. V. Neroev; S. V. Saakyan; P. A. Ilyukhin; V. V. Valskiy; M. V. Ryabina; A. Yu. Novikova (Российский офтальмологический журнал, 2018)
Purpose: to evaluate the efficiency of brachytherapy treatment in capillary retinal hemangioma and the emerging complications. Material and methods. Between 2005 and 2014, 18 patients with capillary hemangioma of the retina (11 females and 7 males, mean age 29 ± 13.9 years) were treated, 8 patients had monocular and 10 patients had binocular lesion. In 12 cases, capillary hemangioma of the retina was associated with Hippel - Lindau disease, in 6 cases a sporadic tumor appeared. 90Sr and 106Ru ophthalmic applicators were used. In 7 eyes, brachytherapy was preceded by laser coagulation. After local irradiation, the patients were followed up for 1 month to 3 years. Results. The pathological process was stabilized in 13 eyes. 5 eyes, no later than 3 months after the procedure, developed a severe radiation reaction, total retinal detachment, and recurrent hemophthalmos, which later, after 6 months or more, led to the development of neovascular glaucoma. In one case, the eye had to be enucleated due to terminal painful glaucoma. In 3 eyes despite tumor regression, retinal detachment persisted over the follow-up period, although the macular area remained unaffected. Complicated cataract (12 eyes), neuroretinopathy (2 eyes), appearance of new capillary hemangiomas (1 eye), increased epiretinal fibrosis (4 eyes), and secondary central chorioretinal dystrophy (2 eyes) were observed over the period of up to 2 years. Conclusion. In most cases, brachytherapy of retinal capillary brings about a satisfactory anatomical result. However, in order to reduce postoperative complications and improve the functional result, a thorough preoperative selection of patients is needed, which should take into account the initial retinal status. For citation: Neroev V.V., Saakyan S.V., Ilyukhin P.A., Valskiy V.V., Ryabina M.V., Novikova A.Yu. The role of brachytherapy in the treatment of retinal capillary hemangiomas. Russian ophthalmological journal. 2018; 11 (3): 5-10 (In Russian). doi: 10.21516/2072-0076-2018-11-3-5-10